A new species of Aethra (Decapoda: Brachyura: Aethridae) from the early Serravallian (middle Miocene) of the Medobory Hills (Ukraine) - Ossó, Àlex (Zootaxa, 2018)
A new species of the genus Aethra (A. stalennyii n. sp.) from the Badenian (middle Miocene) reef frameworks of the Maksymivka quarry in the Medobory Hills, near Ternopil (Ukraine) is described herein. Aethra stalennyii n. sp. represents the first fossil occurrence of the genus known to date. Aethra stalennyii n. sp. inhabited a very similar habitat to those all the extant congeners live in. The presence of Aethra in the middle Miocene of the Central Paratethys adds further emphasis on close affinities between Tethyan reef-associated decapod assemblages and their modern counterparts in the Indo-West Pacific waters. Aethra stalennyii n. sp. represents the first report of Aethra in the fossil record. Possible origin of the genus and subsequent migration eastward is discussed.